Klasterisasi Lagu Populer dan Eksplorasi Subgenre Spotify 2024 dengan K-Medoids - Alfia Nurlaili Tahiyat; Bima Maulana; Ade Eka Saputra; Lusiana Efrizoni; Rahmaddeni Rahmaddeni (Pusat Riset dan Inovasi Nasional, 2025)
Spotify's genre classification system remains too broad, often grouping songs with distinct characteristics into the same category. For example, Pop Ballads and Dance Pop are frequently classified under